Management of the aortic root in type A aortic dissection: A valve sparing approach. Issue 5 (28th September 2020) - Mohamed Ahmed, Eltayeb; Chen, Edward P.
Abstract: Background: Type A acute aortic dissection (TAAAD) is rapidly fatal without emergency repair. Surgical outcomes have improved over the years with improvements in technique and postoperative care. Classically, supracomissural aortic replacement has been the standard of care. However, reintervention rates, particularly on the aortic root in certain groups of patients, shifted the focus towards improving long‐term results of surgical repair. With regard to the aortic root, root replacement has been the gold standard. However, the surgical community realized that valve replacement in itself is a disease, and valve sparing aortic root replacement (VSRR) took center stage in the care of these patients. Methods: We searched the Pubmed and EMBASE databases for articles related to VSRR and composite valve conduit (CVC) root replacement, and the long‐term results of these techniques in TAAAD. Results: Supracomissural repair is limited by reintervention, and CVC results are affected by complications related to the prosthetic valve. Conversely, VSRR is associated with good short‐term outcomes, improvement in quality of life, and it is durable. Conclusion: VSRR is a sound technique in TAAAD in experienced hands.